2023
DOI: 10.1200/jco.22.02212
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Landscape of Metastatic Cancer Survivorship: Reconsidering Clinical Care, Policy, and Research Priorities for the Modern Era

Abstract: Author affiliations and support information (if applicable) appear at the end of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 54 publications
0
31
0
Order By: Relevance
“…Whereas past reviews found survivorship topics covered included financial burden, disparity (e.g., race and ethnicity, rural, access to care), health care delivery, and communication, the present review found these survivorship topics were infrequently addressed in studies of patients with advanced gynecological cancer. Similar gaps in metastatic cancer survivorship research have been identified 59 . Additional issues that may impact survivorship and therefore require attention includes nutritional status and physical condition; indeed, in the identified papers there was a lack of objective outcomes reported relating to these factors.…”
Section: Discussionmentioning
confidence: 63%
“…Whereas past reviews found survivorship topics covered included financial burden, disparity (e.g., race and ethnicity, rural, access to care), health care delivery, and communication, the present review found these survivorship topics were infrequently addressed in studies of patients with advanced gynecological cancer. Similar gaps in metastatic cancer survivorship research have been identified 59 . Additional issues that may impact survivorship and therefore require attention includes nutritional status and physical condition; indeed, in the identified papers there was a lack of objective outcomes reported relating to these factors.…”
Section: Discussionmentioning
confidence: 63%
“…19,[24][25][26][27][28] The definition of healing and patients' healing needs can evolve over time as evidenced in this study, which has implications for cancer survivorship-as patients live longer with multiple treatments and toxicities, the symptom burdens and unmet needs accumulate. [29][30][31] There are also important implications for promoting interpersonal communication training for clinicians to become more effective healers in their therapeutic interactions with patients. [32][33][34][35][36] This study has limitations to consider.…”
Section: Discussionmentioning
confidence: 99%
“…There is an emerging population of people with advanced or metastatic cancer [ 1 , 2 ] (i.e., solid or hematological malignancies that are treatable yet predominantly incurable [ 3 , 4 ]) who are likely to have different care goals and face unique care challenges compared to those with early-stage or localized disease or those nearing the end-of-life [ 5 7 ]. The complex nature of advanced or metastatic cancers and their treatment sequelae is exemplified by varied disease trajectories that includes periods of disease stability, disease progression with the potential for further therapy, and possibility of sudden transition to end-of-life care [ 7 , 8 ]. Significantly higher physical, financial, spiritual, and psychosocial symptom burden results, with advanced or metastatic cancer survivors and caregivers thus engaging with the healthcare system at a higher frequency and intensity than those with early-stage disease [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The complex nature of advanced or metastatic cancers and their treatment sequelae is exemplified by varied disease trajectories that includes periods of disease stability, disease progression with the potential for further therapy, and possibility of sudden transition to end-of-life care [ 7 , 8 ]. Significantly higher physical, financial, spiritual, and psychosocial symptom burden results, with advanced or metastatic cancer survivors and caregivers thus engaging with the healthcare system at a higher frequency and intensity than those with early-stage disease [ 8 , 9 ]. Despite continually improving outcomes, people with advanced or metastatic cancer may be intentionally or inadvertently denied quality survivorship care that has become emphasized for those living with and beyond curable cancers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation